Application of bone turnover markers in skeletal and extra-skeletal conditions in children and adults - Agnieszka Postępska; Przemysław Sikora (Pediatria Polska)
The assessment of bone health is challenging. It comprises bone histomorphometry, imaging techniques and laboratory parameters including bone turnover markers (BTMs). The latter are bone-derived products which can be measured in biological fluids, including blood and urine. Considering the disadvantages and limitations of imaging techniques, BTMs serve as an additional, non-invasive source of information about the metabolic activity of the entire skeleton. BTMs have found applications as research and clinical tools in a wide range of skeletal and extra-skeletal conditions, including diagnosis and treatment of osteoporosis. Unfortunately, their utility in routine clinical practice, especially in children, is still limited due to heterogenous methodology, intra- and inter patient variability, and a paucity of accurate reference ranges and approved guidelines. Therefore, there is a need for standardized clinical trials on currently available and new BTMs.